THE EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON THE GOOGLE CLASSROOM AGAINST LEARNING MOTIVATION - Nabila Nada Tuffahati; Jaka Nugraha (LPPM STMIK Pringsewu, 2021)
This study aims to determine: (1) the effect of Perceived Usefulness on the use of Google Classroom on learning motivation, (2) the effect of Perceived Ease of Use on the use of Google Classroom on learning motivation, (3) the effect of Perceived Usefulness and Perceived Ease of Use on the use of Google Classroom on learning motivation. This research consists of several constructs. Those are Perceived Usefulness (X1), Perceived Ease of Use (X2) Learning Motivation (Y). The data collection method used is a research questionnaire whose data are analyzed using the SPSS 25 program with 75 respondents from Class 2017, students of Office Administration Education, Faculty of Economics, Surabaya State University. This research will be conducted with quantitative methods using multiple linear regression analysis. The results of this study indicate that there is a significant effect of Perceived Usefulness on learning motivation. It can be seen from the T-test results on X1, which is significant (X1) 0.001 <0.05, so that H1 is accepted. Perceived Ease of Use has a considerable influence on learning motivation. It can be seen from the T-test results on X2 with a significant value of 0.003 <0.05, so that H2 is accepted. The influence of Perceived Usefulness and Perceived Ease of Use on learning motivation has a percentage of 51.3%. Meanwhile, other variables that influence and are examined yet in this study amounted to 48.7%. It shows that if the respondent feels that Google Classroom is valuable and easy to use, the respondent will use Google Classroom.